Attitudes to Chronic Poverty in the "Global Village" - Armando Barrientos; Daniel Neff (German Institute of Global and Area Studies (GIGA), 2010)
The paper explores attitudes to chronic poverty in a cross-section of developed and developing countries based on data from the World Values Survey Wave Three (1994-1998). The analysis finds a consistent belief among a majority of respondents that poverty is chronic. This paper also explores the factors that influence public attitudes to chronic poverty and finds that interests, position, knowledge, and shared values relating to social justice are important. – – In dem vorliegenden Arbeitspapier werden Haltungen zu chronischer Armut anhand von Querschnittsdaten aus Entwicklungs- und Industrieländern auf der Basis der dritten Runde des World Values Survey (1994-1998) untersucht. Die Ergebnisse verdeutlichen, dass die Mehrheit der Befragten Armut als chronisch ansieht. Die Untersuchung zeigt zudem die jeweiligen Einflussfaktoren auf die öffentliche Meinung zu chronischer Armut auf, von denen insbesondere Interessen, Stellung, der Wissensstand als auch gemeinsame Werte bezüglich sozialer Gerechtigkeit von Bedeutung sind.
Keywords: I30; I32; I38; 300; attitudes; chronic poverty; Armut; Meinung; Soziale Werte; Welt